Rogue empires : contracts and conmen in Europe's scramble for Africa - Press, Steven (Harvard University Press, 2017)
Rogue Empires takes a new look at the origins and consequences of a key moment in European History: the Berlin Conference of 1884-1885. Drawing on archival research conducted in ten countries and three languages, the book argues that the flood of rogue empires in Africa came about due to a short-lived European obsession with events happening far away, in Southeast Asia. European investors there had recently promoted an idea of buying empires through "private" purchases of sovereignty: full control over a place's resources and people, with neither monitoring by third parties, nor any accountability to a nation, nor, in most cases, the awareness of affected indigenous peoples. Once this idea made its way back around the world to European capitals, it inspired a number of important figures, notably German chancellor Otto von Bismarck and British Prime Minister William Gladstone, to support a string of copycat ventures in Sub-Saharan Africa.--